Brief Version of Caffeine Expectancy Questionnaire in Brazil - Mendes, Guilherme Falcão; Reis, Caio Eduardo Gonçalves; Nakano, Eduardo Yoshio; Zandonadi, Renata Puppin (Frontiers in Nutrition, 2021)
The use of extensive questionnaires has the limitation of filling time bias, related to the ability to focus and accurately respond to many items, justifying the necessity for a brief version. This study aimed to build a brief version of the Caffeine Expectancy Questionnaire in Brazil (B-CaffEQ-BR) composed of 21 items divided into seven factors, with as adequate consistency and reproducibility as the full version. Quantitative procedures using statistical modeling were applied using the CaffEQ-BR (full version) database keeping the Mean Absolute Error (MAE) (based on the full version) <0.5 and Cronbach's α and Intraclass Correlation Coefficient (ICC) ≥0.7. The expert panel (n = 3), in a blind design, evaluated the semantic structuring within the options indicated by previous statistical modeling until the agreement of the expert panel. The participants (n = 62), Brazilian adults who were regular caffeine consumers (175.8 ± 94.4 mg/day), of whom 62.9% were women, 33.1 ± 9.7 years, 24.5 ± 3.8 kg/m2, and 62.9% of whom self-identified as white, were asked to respond twice to the online questionnaire in 48–72 h. The first sample (n = 40) tested interobserver reproducibility with the double application of B-CaffEQ-BR. Another sample (n = 22) answered the CaffEQ-BR (full version) and B-CaffEQ-BR, and the last sample (n = 18) performed the reverse process. The B-CaffEQ-BR presented excellent internal consistency (Cronbach's α ≥ 0.729) and overall reproducibility (ICC ≥ 0.915) for the entire questionnaire and its seven factors. The B-CaffEQ-BR can be a valuable tool in caffeine research with the Brazilian adult population.